1983
DOI: 10.1002/cne.902170308
|View full text |Cite
|
Sign up to set email alerts
|

The number of neurons in the different laminae of the binocular and monocular regions of area 17 in the cat

Abstract: The number of neurons in individual laminae of area 17 was determined separately for both the binocular and the monocular regions in the left hemisphere of six cats. The number of neurons/mm3 of tissue was obtained for each lamina by using the method of size-frequency distribution applied to neuronal nuclei. The number of neurons per unit of cortical surface could then be calculated from measurements of layer thickness. The number of neurons/mm3 of tissue for the total cortical thickness is on the order of 48,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 25 publications
4
64
1
Order By: Relevance
“…Feedback connections were 5%, from the infragranular excitatory cells of the second cortical area to the modulatory NMDA synapses of supragranular cells in the rst cortical area. The synapse-to-neuron ratio in this model was consistent with experimental ndings (Beaulieu & Colonnier, 1983, 1985. The extrinsic, interareal connections were exclusively excitatory.…”
Section: Integrate and Fire Modelsupporting
confidence: 74%
“…Feedback connections were 5%, from the infragranular excitatory cells of the second cortical area to the modulatory NMDA synapses of supragranular cells in the rst cortical area. The synapse-to-neuron ratio in this model was consistent with experimental ndings (Beaulieu & Colonnier, 1983, 1985. The extrinsic, interareal connections were exclusively excitatory.…”
Section: Integrate and Fire Modelsupporting
confidence: 74%
“…These authors concluded that tissue shrinkage under such conditions was minimal (< I%), and a recent study of rat hippocampus has reached a similar conclusion (West et al, 1988). However, other authors have reported and corrected for substantial shrinkage in similar studies (e.g., Beaulieu and Colonnier, 1983). Shrinkage may affect various components of the tissue unequally, and the processes of injected and filled cells may corrugate rather than reducing in length if shrinkage occurs.…”
Section: Slicepreparationmentioning
confidence: 75%
“…Anatomical studies indicate that the total number of synapses formed by the chandelier cells on the axon initial segment is between 20 and 43 (Somogyi et al, 1982;Farinas and DeFelipe, 1991 (Beaulieu and Colonnier, 1983;Gabbott and Somogyi, 1986), and S j u axo2/3 ϭ 3300 ϫ n j axo2/3 because a chandelier cell forms ϳ3300 synapses in layer 2/3 (Somogyi et al, 1982;Freund et al, 1983). …”
Section: Synapses Made By Chandelier Cells ( J ϭ J Axo2/3 )mentioning
confidence: 99%
“…Beaulieu and Colonnier (1983) counted for each cortical layer the number of cell bodies under a square millimeter of cortical surface in cat area 17. Multiplying these numbers with the total surface area of one cortical hemisphere, which for the cat is 399 mm 2 (Anderson et al, 1988), we obtained the total number of neurons per layer.…”
Section: Basic Properties Of Cortical Layersmentioning
confidence: 99%